EFFECT OF JOB SATISFACTION TOWARDS ORGANIZATIONAL BEHAVIOR ORGANIZATIONAL BEHAVIOR (OCB) IN EMPLOYEES IN THE FIELD OF PT ARTANUSA BETON SAMARINDA - Hika Matul Muka Romah Sodiq (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
Companies that pay less attention to the conditions of their employees tend to cause employee dissatisfaction. Companies need to improve employee job satisfaction because employees feel satisfied. then the employees will provide remuneration to the company and weigh the attitude of the Citizenship Organization (OCB). OCB itself shows the attitude of employees who are willing to work more than what is determined by the company. This attitude will increase employee productivity which in turn has a good impact on the company. This study aims to see the influence of the sub-variables of job satisfaction, namely the job itself (X1), salary (X2), promotion (X3), supervisors (X4) and co-workers (X5) on the OCB (Y) variable. The subjects of this study were employees of the field section of PT Artanusa Beton with a population of 95 people. The sample in this study were 62 respondents using purposive sampling technique with the criteria of respondents who have worked for more than one year. Data analysis was performed using multiple linear regression analysis. The results of this study indicate that simultaneously there is a significant influence between job satisfaction variables consisting of the job itself, salary, promotion, supervisors and co-workers on the OCB variable. The partial variables of the job itself, salary, supervisors and co-workers have a significant effect on OCB. While promotion has no significant effect on OCB and the variables that have dominant influence on OCB are colleagues.